Simultaneous Determination of Acetyl Salicylic Acid and Acetaminophen in Acetaminophen-Caffeine-Aspirin (ACA) Tablets by FT-IR/ATR Spectrometry with Multivariate Calibration Data Treatment - Sohrabi, M.R.; Davallo, M.; Tadayyon, F.; Nabipoor, F.; Khamneifar, A. (Asian Journal of Chemistry, 2016)
A simultaneous method based on Fourier transform infrared (FTIR) was developed for the determination of acetyl salicylic acid (aspirin) (ASA) and acetaminophen coupled with an attenuated total reflectance (ATR) accessory. The method was based on dissolving the drug powder in ethanol followed by FTIR spectroscopy and prediction of the active components using partial least squares (PLS) regression analysis. Although the drug mixture showed some regions of spectra overlapping, but they were simultaneously determined with high accuracy, without interference from tablet excipients. A comparison is represented with related multivariate method of principal component regression (PCR) analysis, which is shown to yield less reliable results. In the analysis of real and synthetic samples, precise and accurate values were obtained by PLS-FTIR with less than 3% standard errors. Finally, the results were compared with standard method (USP) and good agreements were obtained by PLS-1.